Un Canada et un Québec qui conjuguent le passé différemment : le poids du passé dans le rapport préliminaire de la Commission royale d’enquête sur le bilinguisme et le biculturalisme - Valérie Lapointe-Gagnon (Conserveries Mémorielles)
This article is about a source, the Preliminary Report of the Royal Commission on Bilinguism and Biculturalism, that permits to enter, through the fragments of testimonies of Canadian citizens and their analysis by the commissers, in the Quebecers and Canadians’ memories, which evolve in two ways apart. Published in 1965, the Preliminary Report had the effect of a bomb in revealing the intensity of the Canadian crisis, which threatens, according to the commissers, the Canadian unity. How does the tracks of past manifest themselves within the report? What does the document reveal on the Canadian and Quebecois memories? Where does the crisis described by commissers draws its source? Such are the questionings which will interest us. Through the analysis of the preliminary report, all the complexity of the Canado-Quebecois connections is appearing. Also appears some solutions which are still of a profound actuality.